The zinc cluster transcription factor Ahr1p directs Mcm1p regulation of Candida albicans adhesion - Askew, Christopher (2010)
Biofilm development by Candida albicans requires cell adhesion for the initial establishment of the biofilm and the continued stability after hyphal development occurs; however, the regulation of the process has not been fully established. Using chromatin immunoprecipitation coupled to microarray analysis (ChIP-chip) we have characterized a regulon containing the Mcm1p factor that is required for the initial surface adhesion during biofilm formation. In the yeast Saccharomyces cerevisiae several Mcm1p regulons have been characterized in which regulatory specificity is achieved through cofactors binding a sequence adjacent to the Mcm1p binding site. This new Mcm1p regulon in C. albicans also requires a cofactor, which we identify as the transcription factor Ahr1p. However, in contrast to the other yeast regulons, Ahr1p alone binds the target promoters, which include several key adhesion genes, and recruits Mcm1p to these sites. Through transcription profiling and qPCR analysis, we demonstrate that this Ahr1p–Mcm1p complex directly activates these adhesion genes. When the regulatory circuit was disrupted by deleting AHR1, the strain displayed reduced adherence to a polystyrene surface. We also demonstrate a role for the regulon in hyphal growth and in virulence. Our work thus establishes a new mechanism of Mcm1p-directed regulation distinct from those observed for other Mcm1p co-regulators.